Recent developments in the theory of Walsh series - William R. Wade (International Journal of Mathematics and Mathematical Sciences)
We survey research done on the theory of Walsh series during the decade 1971-1981. Particular attention is given to convergence of Walsh-Fourier series, gap Walsh series, growth of Walsh-Fourier coefficients, dyadic differentiation, and uniqueness of Walsh series.